Environmental factors influencing hygiene practices among pupils in selected public primary schools in Kiambu County, Kenya - Ndungu, Veronica; Juma, Joseph; Mburu, Samuel (International Journal Of Community Medicine And Public Health, 2025)
Background: Hygiene practices, including hand washing with soap and water, are essential for preventing diseases like diarrhoea, especially in developing countries. Poor hygiene, inadequate water, and sanitation contribute to over 60% of the disease burden among students. This study investigates how hygiene promotion approaches, such as school-led sanitation programs, affect cleanliness practices among public primary school students in Kiambu County, Kenya. Methods: Analytical cross-sectional study design was used and 121 participants in public primary schools from Gatundu South, Juja, Ruiru, and Kiambu sub-counties. Data was collected using administered structured questionnaire, and Key Informant Interview. Quantitative data analysis was conducted using SPSS version 29.0 and involved univariate and bivariate analysis. Qualitative data was analyzed by thematic content analysis. Results: The study involved 121 respondents, aged 22-59 years (mean age 38.29±8.1), with 52.9% being female and 49.6% had undergraduate degrees, and 39.7% were senior teachers. The pupil-to-toilet ratio in the schools was 1:29, which did not meet the recommended standards for boys (1:36) but met the standard for girls (1:24). Hygiene promotion activities included parades (66.1%), classroom sessions (61.2%), and health clubs (60.3%). Factors like observing, demonstrating, and inspecting hygiene practices were strongly linked to improved handwashing, with ORs of 5.4, 8.8, and 5.8, respectively. Conclusions: The study found strong associations between hygiene practices and implementors’ expertise, with significant environmental factors influencing student hygiene. The public health and community health volunteers should take more active role in dissemination timely and accurate information on hygiene and health promotion.